Quality of fresh and stored eggs related to the permanence time in nest boxes from cage-free aviary housing system (Research, Society and Development, 2021)
The aim of this study was to investigate whether the permanence of cage-free eggs in the nests compromises their internal quality. 660 commercial Isa Brown laying eggs, 31 weeks old, were distributed in two independent studies. In study 1, the quality of 180 fresh eggs submitted to different permanence times in the nest (0h, 2h, 4h, 6h) was evaluated. Egg weight, albumen height, Haugh Unit and Yolk Index were analyzed. In study 2, 480 eggs were stored in a 4 x 5 factorial scheme [length of permanence in the nest (0h, 2h, 4h, 6h) vs storage period (0, 7, 14, 21 and 28 days)]. Albumen height, Haugh Unit, Yolk Index, yolk and albumen pH, lipid oxidation and egg weight loss were evaluated. Significant changes were observed for Haugh Unit and albumen height in fresh eggs, as the eggs remained in the nest, with lower values (P